Sosialisasi Berantas Stunting “BENING” dan Praktik Pengelolaan Sampah Masakan sebagai Upaya Pencegahan Stunting - Adik Annisa Fitri Suryani; Hammam Fauzi; Afi Imroatul Mufidah; Azizah Sofiana; Elvina Dhamayanti; Kusuma Ayu Astria; Miftakhul Khusna Kurniawati; Prasetyo Nugroho; Rachmijanti Anggreana; Yustri Apri Margarini; Kenfitria Diah Wijayanti (Edumedia Solution, 2022)
Stunting is a condition of failure to thrive in children (body and brain growth) due to chronic nutrition for a long time so that children are shorter than normal children their age and have delays in intelligence. In Indonesia, the incidence of short toddlers ranks 5th in the world. Factors causing stunting can be classified into two environmental factors, namely the health of pregnant women and those who are less healthy. To overcome this problem, Group 02 KKN UNS 2022 held a socialization on eradicating stunting and food waste management practices, entitled BENING socialization